A new steroid with 7β, 8β-epoxidation from the deep sea-derived fungus Aspergillus penicillioides SD-311. Issue 9 (2nd September 2021) - Chi, Lu-Ping; Yang, Sui-Qun; Li, Xiao-Ming; Li, Xiao-Dong; Wang, Bin-Gui; Li, Xin
Abstract: 7β, 8β-epoxy-(22 E, 24 R )-24-methylcholesta-4, 22-diene-3, 6-dione (1 ), a new steroid, along with five known analogues (2 –6 ), was isolated from the deep sea-derived fungus, Aspergillus penicillioides SD-311. Strikingly, 1 possessed a rare 7, 8-epoxidation moiety. Meanwhile, this is the first time to report natural products from this fungus species. The structures were established by extensive spectroscopic analysis. The absolute configuration was determined by X-ray diffraction experiments. Compound 1 showed antibacterial activity against Vibrio anguillarum with MIC value of 32.0 µg/mL, while 2 displayed inhibitions against Edwardsiella tarda and Micrococcus luteus with MIC values both of 16 µg/mL. Graphical abstract: UF0001